Trans-Atlantic genetic uniformity in the rare snowbed sedge Carex rufina - Westergaard, Kristine; Alsos, Inger Greve; Engelskjøn, Torstein; Flatberg, Kjell Ivar; Brochmann, Christian (Conservation Genetics, 2011)
The red-listed, amphi-Atlantic sedge Carex rufina is highly specialized to certain alpine snowbeds, and threatened by current changes in snow cover duration and moisture conditions. Here we address its range-wide genetic diversity, history, and conservation using amplified fragment length polymorphisms (AFLPs). Despite extensive primer testing, we detected very low overall diversity (4.1% polymorphic markers). Only a single AFLP phenotype was found throughout Norway and across the Atlantic to Iceland and Greenland, while another was found in Canada, suggesting glacial survival in one East and one West Atlantic refugium. East Atlantic C. rufina has probably been heavily bottlenecked in a small refugium, possibly situated within the maximum limits of the ice sheets. Its lack of diversity is likely maintained through local clonal growth causing longevity of genotypes. Habitat availability appears as the main limiting factor for C. rufina, and its currently occupied habitats need to be preserved to ensure its long-time survival.